Analysis of DNA Microarrays by Non-Destructive Fluorescent Staining Using SYBR® Green II - C. Battaglia; G. Salani; C. Consolandi; L. Rossi Bernardi; G. De Bellis (BioTechniques)
A simple, non-destructive procedure is described to determine the quality of DNA arrays before they are used. It consists of a preliminary staining step of the DNA microarray by using SYBR® green II, a fluorophore with specific affinity for ssDNA, followed by a laser scan analysis. The surface quality, integrity and homogeneity of each DNA spot of the array can thus be assessed. After this preliminary control, which may avoid further analytical steps that lead to the waste of precious biological samples, a fully reversible staining procedure is performed that produces an array ready for subsequent use.